Analyzing space efficiency in Japanese tall buildings - Hüseyin Emre Ilgın; Özlem Nur Aslantamer (Journal of Asian Architecture and Building Engineering)
Space efficiency in Japanese tall buildings holds substantial significance, shaped by financial, societal, and environmental imperatives. Nevertheless, comprehensive studies addressing spatial efficiency in such towers remain scarce. To bridge this gap, this article undertakes a quantitative spatial analysis of 40 Japanese tall buildings through BIM/CAD-based floor plan evaluations and comparison of net-to-gross and core-to-GFA efficiency ratios. Key findings include: (1) mixed-use and office typologies, central cores, and prismatic massing dominate contemporary Japanese high-rise design; (2) composite structures with shear-walled frame systems are prevalent; and (3) the average net-to-gross ratio is 75%, with core areas occupying 23% of total GFA. The efficiency metrics range from 64% to 85% for net-to-gross ratios, and from 13% to 34% for core-to-GFA ratios. This research offers practical insights for stakeholders – especially architects and planners – to support more efficient and sustainable high-rise design strategies in Japan.